Pendampingan Strategi Digital Marketing untuk Meningkatkan Penjualan Produk Semprong Mawar Cemal Cemil Echo di Desa Pomahan - Sumani Sumani; Nanik Setyowati (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Pomahan is one of the villages in Pulung District, Ponorogo Regency, East Java Province which has the potential for various Micro, Small and Medium Enterprises (MSMEs), especially entrepreneurs and home industries. This business has become the livelihood of the people in Pomahan Village, Pulung District, Ponorogo Regency. In Pomahan Village itself there are many Micro, Small and Medium Enterprises (MSMEs) who innovate in opening their businesses but are lacking in maximizing the potential of social media as one of their markets, especially in the